Groundbreaking guys : 40 men who became great by doing good - Peters, Stephanie True, 1965- (Little, Brown and Company, 2019)
Presents short profiles of forty diverse men who have made a positive impact on the world, ranging from an escaped slave, a Supreme Court Justice, and diplomats to activists and musicians.